2013
DOI: 10.1002/pssa.201330150
|View full text |Cite
|
Sign up to set email alerts
|

Influence of iron contaminations on local and bulk magnetic properties of nonfunctionalized and functionalized multi‐wall carbon nanotubes

Abstract: We investigated Fe‐phases of iron complexes embedded in nonfunctionalized (as‐prepared) and functionalized multi‐wall carbon nanotubes (MWCNTs). Mössbauer spectroscopy is a very sensitive tool to study chemical states of iron compounds embedded in MWCNTs. It showed that the chemical treatment of the as‐prepared MWCNTs caused release of about 84% of iron and modification of the remaining iron compounds. In as‐prepared and carboxylated MWCNTs almost 80 and 75% of iron complexes in a form of Fe3C exhibited magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…The thermal evolution of magnetization normalized to the mass of the unground samples was presented and discussed in [ 43 ]. In our previous study, the process of MWCNT purification by functionalization was observed to cause the iron contamination to drop in these nanotubes by about 90%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The thermal evolution of magnetization normalized to the mass of the unground samples was presented and discussed in [ 43 ]. In our previous study, the process of MWCNT purification by functionalization was observed to cause the iron contamination to drop in these nanotubes by about 90%.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 7 , examples of high-resolution images of functionalized MWCNTs, ground in the agate and steel mill, are shown. Their outer and inner surfaces are no longer smooth, as in unmilled nanotubes ( Figure 7 a,b; [ 43 ]). One can also observe the fracture sites of several walls at once ( Figure 7 d,e,g).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polypropylene (PP) non-woven fabric with fiber diameter sizes ranging from 0.2 to 30 µm were supplied by Amazon Filters Ltd. Multiwall carbon nanotubes (MWCNT), manufactured by CNT CO., LTD (South Korea), were used after purification with concentrated nitric acid (68% HNO3, POCH) according to the procedure described by Jamrozik and coauthors (Jamrozik et al 2014). For synthesis of iron oxy(hydroxide) nanoparticles, iron(III) chloride hexahydrate (FeCl3•6H2O, Chempur), urea (NH2CONH2, POCH) and distilled water prepared with HLP10p Hydrolab (Poland) were used.…”
Section: Materials and Reagentsmentioning
confidence: 99%